Relationship Of Stress With Blood Pressure In Elderly >60 - Ganjar Safari; Susi Yulianingsih; Waryantini Waryantini (Jurnal KESANS : Kesehatan dan Sains, 2022)
Blood pressure is the pressure at which blood circulates in the blood vessels. Changes in blood pressure are influenced by various factors, one of which is stress conditions. In general, stress can stimulate an increase in blood pressure, which can be at risk for illness, especially in the elderly. Therefore, this study aims to determine the relationship between stress and blood pressure in the elderly >60 years during the Covid-19 pandemic in the Pameungpeuk Community Health Center, Bandung Regency. Correlational analytic research method with cross-sectional approach. Samples of 30 elderly people over 60 years were taken by incidental sampling technique. The research instrument used a data questionnaire sheet and the results of blood pressure checks on the respondents. Spearman rank is used for statistical tests with an error rate of 5%. The results showed that most of the respondents' stress levels experienced moderate stress (46.7%) and almost all of the respondents' blood pressure increased or hypertension (63.3%). Spearman Rank test proved that there is a positive and significant relationship between stress and blood pressure in the elderly > 60 years (significant value = 0.023 and correlation coefficient 0.414). Thus, especially for the elderly to be able to manage stress well so that an increase in blood pressure can be prevented, such as by maintaining a healthy lifestyle.